Anaesthesiologic proceedings in perioperative bleedings in patients with hepatic failure - Przesmycki, Krzysztof; Jaskowiak, Robert (Menopause Review/Przegląd Menopauzalny, 2010)
A perioperative risk is increased in patients with advanced liver dysfunctions and is much higher in emergency operations than in elective surgeries. Perioperative mortality depends on the level of liver damage and is assessed using Child’s classification where patients are assigned to three groups A, B and C according to five easily-assessed parameters: bilirubin concentration (A 3.0 mg/dl), albumin concentration (A > 3.5, B 3.0-3.5, C < 3.0 g/dl), intensification of ascites and encephalopathy (A none, B easy to control, C difficult to control) and nutritional status (A perfect, B good, C poor). Additionally, the assessment of prothrombin time may be helpful. Mortality for each group A, B and C is 10%, 31% and 76%, respectively. The classification also significantly correlates with such complications as bleeding, renal failure, wound dehiscence and sepsis. The main cause of death is multiorgan failure in sepsis. In 1996, the ASA (American Society of Anesthesiologists) recommended critical values for the number of platelets, prothrombin time and fibrinogen concentration which are required for transfusions of blood products in massive transfusions and microcapillary bleeding: (1) transfusion of platelet concentrates is usually recommended if the number of platelets is 1.5 the normal range, (3) transfusion of cryoprecipitate is recommended if the concentration of fibrinogen is < 80-100 mg/dl. Transfusion of cryoprecipitate is also recommended in perioperative prophylaxis in non-bleeding patients with fibrinogen deficits or with von Willebrand disease with or without haemorrhagic diathesis. Preoperative preparation which consists of correction of symptoms connected with advanced liver diseases (optimization of parenteral and oral feeding with additional doses of vitamin B1, correction of clotting disturbances by transfusion of FFP and/or cryoprecipitate, reduction of concomitant encephalopathy, prevention of sepsis with prophylactic antibiotic therapy, monitoring of renal function with careful correction of electrolyte disturbances) may significantly improve the results of surgical treatment. Key words: hepatic failure, perioperative bleedings